Influence of Integrated Pressing during Fused Filament Fabrication on Tensile Strength and Porosity / Siti Najatul Aishah Majid...[et al.] - Aishah Majid, Siti Najatul; Alkahari, Mohd Rizal; Ramli, Faiz Redza; Maidin, Shajahan; Tan, Chee Fai; Sudin, Mohd Nizam (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Additive manufacturing or 3D printing is a technology that built 3D objects by adding material layer-by-layer. There are tremendous studies have been conducted regarding this new emerging technology to transform the printed part from being a prototyping tool to a manufacturing process that can create durable and functional goods, and comparable to the traditional manufacturing processes. Therefore, this study proposes a new method of Fused Filament Fabrication (FFF) by integrating with mechanical pressing where a roller is used to improve the strength and porosity of the printed part during processing. This study focuses on the low-range RepRap 3D printer. Mendel RepRap was used to print the samples, and the material of Acrylonitrile-butadiene-styrene (ABS) was used for this study. The samples printed from both techniques, normal FFF and FFF with pressing were compared with respect to their tensile strength and porosity. The strength of the samples was tested using an Instron machine, and the images of the samples were captured using Scanning Electron Microscope (SEM). Later, Image J software was used to analyze and calculate the percentage of the porosity. Based on the results, the percentage of porosity for the normal FFF is about 20~21% while FFF with pressing shows the smaller value that ranges from 12~15%. Meanwhile, the tensile strength of the FFF with pressing gave a greater value which is up to 38.34 Mpa.